Preparation and evaluation of dispersible tablets of Trikatu extract - Garg, Dr. Munish (Asian Journal of Pharmaceutics (AJP), 2014)
Traditional Ayurvedic formulations are consumed increasingly as dietary supplements to fight or prevent various types of diseases since ages. â€œTlikatuâ€ (Sanskrit, meaning â€œthree acridâ€), is a mixture of black pepper (Piper nigrum); longÂ pepper (Piper longum); and ginger (Zingiber ofticinale); widely used in Ayurvedic system of medicines to enhance bioavailability. However being consumed in powder form, it is associated with certain limitations of large and uncalculated dose and uncertain quality. To overcome this, the present study was carried out to develop standardized dispersible tablets of Trikatu extracts. Three main ingredients were thus subjected for extraction, screened for phytochemical status using standard markers by highâ€performance thinâ€layer chromatographyhighâ€performance thinâ€layer chromatography and mixed proportionately. A method was then developed to formulate these extracts into dispersible tablets by direct compression method andÂ evaluated for their physicoâ€chemical properties, which have demonstrated good flow properties with zero drugâ€excipientÂ incompatibility, less disintegration time and other requirements within pharmacopoeial limits. This scientifically developedÂ formulation intends to have advantages over the traditional form and thus be able to deliver better therapeutic results.Â  Key words: Highâ€performance thinâ€layer chromatography, piperine, shogaol, standardisation, tablet,Trikatu